C-Reactive Protein : An Important Diagnostic Tool in Neonatal Sepsis - Panchal, Nirav S; Patel, Mehul A (Annals of Pathology and Laboratory Medicine, 2018)
Background: Global burden of pediatric mortality during the very first month of life is around four million per year. In developing country like India, neonatal mortality is as high as one fourth (25%) of the global burden means around one million per year. Among the various common causes, infection or sepsis alone contributes for almost 30-40% of total neonatal deaths. The study is aimed to determine the effectiveness of C-reactive protein (CRP) as a diagnostic tool in neonatal sepsis. Materials and Methods: This is a cohort prospective study. Study included total 123 patients considering inclusion and exclusion criteria. Blood samples were taken from all the patients for blood culture and CRP measurements. Results of blood culture and CRP were recorded and statistical analysis was performed by GraphPad Instat Demo. Results: Out of 123 patients included in the study blood culture was positive in 71 (57.72%) patients and CRP was raised in 72 (58.54%) patients. Sensitivity, specificity, positive predictive value and negative predictive value for CRP were found to be 98.59%, 96.15%, 97.23% and 98.04% respectively. Conclusion: C-reactive protein has high sensitivity and specificity with good positive predictive value and negative predictive value for establishing diagnosis of neonatal sepsis and results with CRP are comparable to those with blood culture.